População mestiça em Sergipe D’el Rey : da ocupação colonial à integração ao Estado Nacional - Vieira, Eden Filipe Santos (2020)
This work investigates how mixed-race persons lived and participated in the constitution of Sergipe Del Rei colonial society and how this population was perceived and considered in the colonial crisis and the constitution of the Brazilian national state. For that, we use documentation produced by the colonial authorities, correspondence, opinions, requisitions, etc., in addition to population maps and other documentation produced by the Sergipe provincial government. We notice that miscegenation was a fundamental factor in framing Sergipe population, both free and slaves. Plus, mixed-races persons play a remarkable role in the Portuguese efforts to defend and occupy the territory. Nevertheless, the mistrust of the colonial authorities weighed on them, which shaped the way the new National State perceived and integrated these subjects.